Toxicology Studies Cells, Drugs and Environment - Cristina Andreazza, Ana; Scola, Gustavo (IntechOpen, 2015)
The increased exposure to toxins, toxicants and novel drugs has promoted toxicology to become one of the most important areas of research with emerging innovative toxicity testing protocols, techniques, and regulation being placed. Since the bioactivation of many toxins and toxicants and its consequences on human health are not clearly known, this book offers a quick overview of cellular toxicology through the cell, drug and environmental toxicity. This book does not strive to be comprehensive but instead offers a quick overview of principle aspects of toxins and toxicants in order to familiarize the key principles of toxicology. The book is divided into three main sections,; the first one discusses the role of mitochondrial dysfunction, oxidative stress and mitochondrial drug development. The second and third sections bring light to forensic toxicology and drug poisoning followed by environmental toxicity.